Direct extraction of coconut oil from its meat - Cubeta, Afrodesia
A study was made on extracting coconut oil from its meat by directly exposing coconut meat to a solvent. Commercial hexane was the solvent used throughout the study. The samples of coconut meat to be extracted were not given any other mechanical treatment except the reduction of its size. Three factors affecting the rate of extraction was considered. these are sample size, temperature, and time of extraction. The size of particles affected most of its extraction rate. A high initial extraction rate was shown in all cases. The experimental results indicated a process of diffusion to control the extraction rate after thirty minutes. The coefficient of diffusion was increased by an increase in temperature and was decreased by an increase in moisture content. It appears that to get most of the oil from fresh coconut meat, one has to cut the meat into at least .001 inches thick, and then expose the solids to a solvent.